177k views
5 votes
Solving the following system using the elimination method. 2x+y=-9
2x-5y=-3

User Jalloh
by
5.2k points

1 Answer

2 votes

Answer:

y=-1 and x=-4

Explanation:

2x+y=-9

and

2x-5y=-3

Multiply the second equation by -1, now we have

2x+y=-9

and

-2x+5y=3

Now you can add both sides of the equations and the x values will cancel, because they are opposites (2x and -2x)

2x+y-2x+5y=-9+3

6y=-6

y=-1

We now know y is -1, so we can substitute back into one of our original equations

2x+y=-9

2x+(-1)=-9

2x=-8

x=-4

y is -1 and x is -4

User Scott Puleo
by
5.3k points